Modelling of n-hexadecane Hydroisomerization and Hydrocracking Reactions on a Mo/Hβ-alumina Bi-functional Catalysts, using the Single Event Concept - Chavarría, J. C. (2004)
Hydrocracking of a long chain paraffin, hexadecane, was carried out on a Mo/Hb-alumina bi-functional catalyst with a weak dehydrogenating function. It was found through an isomerization selectivity analysis that the behavior of the system is away from ideal hydrocracking conditions. To implement for this system the single event concept, until now applied only to systems for which the ideal hydrocracking assumption was valid, a hybrid model that includes the more general case in which reactions on the acid sites are not rate determining was developed. This model was called the single-event-lumped-parameter hybrid (SELPH) model, for it considers fundamental rate constants for the reactions that take place on the acid sites using the single event concept, and lumped rate constants for the reactions on the metal sites. The kinetic coefficients at 533 K were estimated and the agreement between the calculated and experimental data was satisfactory.